Biological Activity of the Selenium Nanoparticles Prepared by Saccharomyces cerevisiae Extract Against Methicillin-Resistant Staphylococcus aureus - Farouq, Maarib Mudhar; Shehab, Zina Hashem (Iraqi Journal of Science, 2026)
There is increased interest in using safe substances for human health, such as creating nanoparticles in an easy and affordable manner to solve the issue of antibiotic resistance. The purpose of this study was to create a new antibacterial agent by using Saccharomyces cerevisiae extract (ScE) to biosynthesize selenium nanoparticles (SeNPs), that inhibit the growth of methicillin-resistant Staphylococcus aureus (MRSA). From 150 swabs taken from various clinical sources from patients at several hospitals in Baghdad, thirty-six S. aureus were isolated and diagnosed based on phenotypic characteristics, biochemical tests and then confirmed by PCR via targeting 16S rRNA gene for S. aureus, and mecA for methicillin-resistant S. aureus diagnosis. Following the use of several appropriate techniques, including FTIR, UV‒vis, AFM, fe-SEM, and XRD, selenium nanoparticles (Sc-SeNPs) were shown to be a chemically stable materials with highly crystalline spherical particles and a maximum grain size of 54.04 nm. A GC-MS analysis was carried out to determine the important active chemicals in the S. cerevisiae extract. Sc-SeNPs appear to offer new viewpoints on their biological efficacy as agents that inhibit bacterial growth and biofilms. This result shows that it has medicinal importance. Therefore, biogenic SeNPs seem to be promising candidates for safe medical use, either by themselves or in combination with conventional biogenic compounds, to inhibit the growth of clinical isolates of S. aureus or to make it easier for antimicrobial drugs to penetrate S. aureus biofilms.